AKSARA INCUNG SEBAGAI IDENTITAS BATIK KERINCI - Dela Puspita Riza; Sulaiman Sulaiman; Rosta Minawati (Pascasarjana Institut Seni Indonesia Padang Panjang, 2022)
The Incung script is a writing system used by the Kerinci comminity. The Script of Incung as a identity in Kerinci Batik aims to identify the identity contained in the Incung Script as motif of Kerinci batik. This study use as a qualitative method with descriptive data that siscuss the data in accordance with the facts encountered in the field with aesthetic studies. Data collection done through literature study, observation, interviews and matrix of data collection. Kerinci batik have two types of batik namely, Kerinci decorative batik and Incung batik with stamp techniques. The color used in the product Kerinci batik is a type of naptol and indigosol. In addition, batik cloth Kerinci is dark inaddition, batik cloth Kerinci is bright in color. The main motif of batik Kerinci is an Incung script combined with Kerinci decorative motifs flora, fauna and heirlooms which are the identity of Kerinci.Keywords: Incung Script; Kerinci; Batik; Aesthetics; IdentityAbstrakAksara Incung merupakan sistem penulisan yang digunakan oleh masyarakat Kerinci. Aksara Incung sebagai identitas batik Kerinci bertujuan untuk mengidentifikasi identitas batik Kerinci. Penelitian ini menggunakan metode kualitatif dengan data deskriptif yang membahas tentang data sesuai fakta yang ditemui di lapangan, dengan kajian estetika. Pengumpulan data dilakukan melalui studi pustaka, observasi, wawancara dan matrik pengumpulan data. Batik kerinci memiliki dua jenis batik yaitu, batik ragam hias Kerinci dan batik Incung dengan teknik batik tulis dan cap. Motif utama batik Kerinci adalah aksara Incung dikombinasi dengan ragam hias Kerinci, motif flora, fauna dan benda pusaka yang merupakan identitas Kerinci.Kata Kunci: Aksara Incung; Batik; Kerinci; Estetika; Identitas